The role of circulating tumor DNA in melanomas of the uveal tract - Mohammed Zeeshan Zameer; Eric Jou; Eric Jou; Mark Middleton (Frontiers in Immunology)
Melanoma of the uveal tract or uveal melanoma (UM) originates from melanocytes of the eye and is the most common intraocular malignancy in adults. Despite considerable advances in diagnostic procedures and treatments, prognosis remains poor in those with advanced disease. Accordingly, although current treatments have an excellent local disease control rate, approximately 50% of patients develop metastatic relapse within 10 years. The high risk for metastatic disease with a variable and often long latency period is thought to be due to early spread of cancer cells disseminating into organs such as the liver, followed by a period of dormancy, before the eventual emergence of radiologically measurable disease. Early detection of disease relapse or metastasis is therefore crucial to allow timely treatment and ultimately improve patient outcome. Recently, advances in minimally-invasive liquid biopsy techniques and biomarkers such as circulating tumor DNA (ctDNA) have demonstrated potential to transform the field of cancer care by aiding diagnosis, prognosis and monitoring of various cancer types. UM is particularly suitable for ctDNA-based approaches due to the relatively well-characterized spectrum of genetic mutations, along with the inherent difficulties and risks associated with getting sufficient tumor samples via traditional biopsy methods. Key potential advantage of ctDNA are the detection of molecular residual disease (MRD) in patients post definitive treatment, and in the early identification of metastasis. This is particularly relevant contemporarily with the recent demonstration of tebentafusp improving survival in metastatic UM patients, and opens avenues for further research to investigate the potential utilization of tebentafusp combined with ctDNA-based strategies in adjuvant settings and early intervention for MRD. The present review illustrates the current understanding of ctDNA-based strategies in UM, discusses the potential clinical applications, explores the potential of utilizing ctDNA in UM MRD in the context of an ongoing clinical trial, and highlights the challenges that need to be overcome prior to routine clinical implementation.